Assessment of the application for renewal of authorisation of selenomethionine produced by Saccharomyces cerevisiae NCYC R397 for all animal species. (11th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the application for renewal of authorisation of organic form of selenium produced by Saccharomyces cerevisiae NCYC R397 (Alkosel ® ) for all animal species. The FEEDAP Panel has delivered two opinions (on 2007 and 2016) on the safety and efficacy of the additive. The additive is characterised as organic selenium mainly selenomethionine (63%); it was initially authorised in 2007 with a content of 2, 000–2, 400 mg Se/kg (97–99 % of organic selenium) and in 2017 the authorisation was further amended to introduce a selenium range of 2, 000–3, 500 mg Se/kg. Additionally, in 2013, the initial authorising Regulation was modified to introduce a maximum supplementation selenium from this additive in feed (0.2 mg Se from Alkosel ® /kg feed). The evidence provided indicates that the additive currently in the market complies with the conditions of authorisation. No new evidence was found that would make the FEEDAP Panel reconsidering its previous conclusions in the safety for target species, consumers and environment. In particular, the Panel confirms that the use of Alkosel ® in animal nutrition does not pose a risk to consumers provided that the maximum selenium supplementation of 0.2 mg/kg feed from Alkosel ® is not exceeded, yet respecting the maximum total selenium in feed of 0.5 mg/kg. Data on the characterisation of the additive and studies on skin/eyes effects led the Panel reconsider the safety for the user, concluding that Alkosel ® is (i) hazardous upon inhalation, (ii) non‐irritant to skin and considered irritant for the eyes and mucosae, and (iii) a dermal sensitiser and likely a respiratory sensitiser. A recommendation regarding the denomination of the additive under assessment was proposed by the Panel.